Analysis of highly potent synthetic opioid nitazene analogs and their positional isomers. Issue 4 (5th December 2022) - Kanamori, Tatsuyuki; Okada, Yuki; Segawa, Hiroki; Yamamuro, Tadashi; Kuwayama, Kenji; Tsujikawa, Kenji; Iwata, Yuko T.
Abstract: Four nitazenes (metonitazene, etonitazene, protonitazene, and isotonitazene), highly potent benzimidazole synthetic opioids, and their four nitro group positional isomers (isonitazenes) were synthesized and analyzed using infrared (IR) spectroscopy, gas chromatography/mass spectrometry (GC/MS), and liquid chromatography/mass spectrometry (LC/MS). In addition, the agonistic activity of all compounds at the human μ‐opioid receptor was measured using a cell‐based assay system. In the IR spectra, characteristic peaks for nitazenes and isonitazenes were observed. In GC/MS, all compounds were well separated on the chromatogram, although distinguishing nitazenes from the corresponding isonitazenes by electron ionization mass spectra was difficult. In LC/MS, all compounds were detected in both positive and negative modes of electrospray ionization. Characteristic fragment ions were observed in the product ion spectra of isonitazenes, enabling nitazenes to be distinguished from isonitazenes. All nitazenes tested demonstrated higher agonistic activity at the human μ‐opioid receptors than the synthetic opioid fentanyl. The agonistic activities of isonitazenes were 11–35 times lower than those of the corresponding nitazenes. However, iso‐etonitazene and iso‐isotonitazene showed moderate activity similar to that of fentanyl, indicating that these drugs could cause poisoning at a comparable level as fentanyl, if these drugs are abused in the future. Abstract : Four nitazenes, benzimidazole synthetic opioids with high potency, and four of their positional isomers isonitazenes were synthesized and analyzed by IR, GC/MS, and LC/MS. Meanwhile, nitazenes tested showed strong agonistic activity at the human μ‐opioid receptors, whereas isonitazenes were several dozen times less active than nitazenes. However, two isonitazenes had moderate activity close to fentanyl.